Cosatu after 40: Part 1: The rise and fall of COSATU’s ‘one industry, one union’ aspiration - Godfrey, Shane; Jacobs, Mario; Macun, Ian (New Agenda: SA Journal of Social and Economic Policy, 2026)
The new wave of trade unions that emerged in South Africa during the 1970s was marked by non-racialism, democracy, and worker control. The unions’ growth, slow at first but then accelerating, was due in part to their organisational effectiveness, the gains they were able to make for workers, and the anti-apartheid politics they adopted. By the early 1980s, the new independent unions had become a major force in the labour relations system and a key part of the fight for political democracy in South Africa.